2021
DOI: 10.3390/plants10071361
|View full text |Cite
|
Sign up to set email alerts
|

Phosphite Reduces the Predation Impact of Poterioochromonas malhamensis on Cyanobacterial Culture

Abstract: Contamination by the predatory zooplankton Poterioochromonas malhamensis is one of the major threats that causes catastrophic damage to commercial-scale microalgal cultivation. However, knowledge of how to manage predator contamination is limited. Previously, we established a phosphite (Pt)-based culture system by engineering Synechococcus elongatus, which exerted a competitive growth advantage against microbial contaminants that compete with phosphate source. Here, we examined whether Pt is effective in suppr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Recently, several chemical compounds have been screened to control Poterioochromonas contamination in microalgal cultures. A recent study showed that addition of phosphite (20 mM) in Synechococcus elongatus culture resulted in a significantly reduced grazing impact of P. malhamensis (Toda et al 2021). It is notable, however, that the beneficial effect of chemical phosphite on inhibiting Poterioochromonas was only studied under laboratory conditions, with the effect of the chemical on microalgal growth remaining unknown.…”
Section: Prevention and Control Methodsmentioning
confidence: 99%
“…Recently, several chemical compounds have been screened to control Poterioochromonas contamination in microalgal cultures. A recent study showed that addition of phosphite (20 mM) in Synechococcus elongatus culture resulted in a significantly reduced grazing impact of P. malhamensis (Toda et al 2021). It is notable, however, that the beneficial effect of chemical phosphite on inhibiting Poterioochromonas was only studied under laboratory conditions, with the effect of the chemical on microalgal growth remaining unknown.…”
Section: Prevention and Control Methodsmentioning
confidence: 99%